Electrical Properties of A Novel Solid Biopolymer Electrolyte based on Algi-nate Incorporated with Citric Acid - Ahmad Fuzlin, Ahmad Faizrin; Ismail, Noor Syahida; Nagao, Yuki; Samsudin, Ahmad Salihin (Makara Journal of Technology, 2019)
In the present study, a novel solid biopolymer electrolyte (SBE) system is introduced by doping citric acid into alginate polymer. A sample of the alginate-citric acid SBE system was prepared via a solution casting technique. Using electrical impedance spectroscopy (EIS), the electrolytes of alginate-citric acid analyzed from 5 Hz to 1 MHz achieved the highest conductivity at 20 wt.% of 5.49 × 10-7 S cm-1. The temperature dependence of various citric acid amounts obeyed the Arrhenius rule with R2~1, where all SBE systems were thermally activated with increasing temperature. The dielectric studies of the alginate-citric acid SBE system showed non-Debye behavior based on data measured using complex permittivity (ε*) and complex electrical modulus (M*) at selected temperature, where no single relation was found in the new biopolymer electrolyte system.